Jogando com os clássicos no Romance d'a pedra do reino e o príncipe do sangue do vai-e-volta - Tereza Pereira do Carmo (2014)
In this dissertation, we seek to develop from the analytical examination of the narrative strategies of intertextuality in the work Romance da pedra do reino e o príncipe do sangue do vai-e-volta , by Ariano Suassuna, and elements of Greek and Latin classical tradition, especially those present in epic and tragedy, namely, myths, poetic places, themes and formal structures. From the concept of intertextuality, the goal was to show that Suassuna dialogues with the classics, retrieving them through what we call an incarnate Brazilian intermixing. The starting point for our analysis was the consideration of the presence of the Oedipus myth in the work in question and observing the peculiar appropriation of it by Suassuna, creating thereby an enchanted mixture that establishes, according to the character Pedro Dinis Ferreira- Quaderna, a new literary genre: the epopeieta2. In this new format, the proposal is to use literary creating resources coming from multiple sources and present in the aesthetics of ancient authors. Apparently, the project of writing the work aims at founding a kingdom. Pedro Dinis Ferreira-Quaderna, the character mentioned before, becomes a storyteller during the narrative - according to an amalgamated model from the Homeric material, and also the tragic model; that, in our view, does not exclude the studies already pointed out by researchers that enhance the medievalism of the work, but adds meaning to this new approach - when reporting the adventures and misadventures of his life and the human condition. Thus, the puzzle of crime and blood to be solved seems to require an appropriation of a more distant literary past for the refounding of the cornerstone of the Brazilian poetic realm.